Mengembangkan Sikap Kooperatif Anak Usia Dini Melalui Metode Proyek - Himmatul Farihah (SELING: Jurnal Program Studi PGRA, 2017)
This study aims to: 1) Describe the application method of the project to develop the ability of the cooperative attitude of early childhood. 2) To describe the result of increased cooperation early childhood through project methods. TK Muslimat Brondong Lamongan selected as a study by the consideration that based on observations conducted by researchers with classroom teachers, not all children in group B had a cooperative attitude is good, especially in carrying out the task group, in collaboration with friends, playing with friends, want to help friends and do not annoy your friends. Kondisdikarenakan activities carried out in the learning activities often use the method of administration tasks. Child ren less given the opportunity to play together, study groups and practice building his own knowledge. Methods project is one strategy that can be selected to develop the principle of play while learning the children in a center of learning and increase social competency early childhood. Results of preliminary observations Social emotional learning ability of the 20 children showed there were 13 children (65%) who lack the social skills of emotional and 7 (35%) of children developing emotional social abilities. The method used in this research is a classroom action research with two cycles of implementation. The results showed that the action through projects implemented method can improve the emotional social abilities in the first cycle increased by 10% to 45%, and in the second cycle increased again by 50% to 90%. Of the overall increase in cognitive ability before action until the second cycle by 60%.